Physical activity as a promising alternative for young people with juvenile idiopathic arthritis: Towards an evidence-based prescription - Rochette, Emmanuelle; Saidi, Oussama; Merlin, Étienne; Duché, Pascale (Frontiers in Immunology, 2023)
Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease in young people. Although biologics now enable most children and adolescents with JIA to enjoy clinical remission, patients present lower physical activity and spend more time in sedentary behavior than their healthy counterparts. This impairment probably results from a physical deconditioning spiral initiated by joint pain, sustained by apprehension on the part of both the child and the child’s parents, and entrenched by lowered physical capacities. This in turn may exacerbate disease activity and lead to unfavorable health outcomes including increased risks of metabolic and mental comorbidities. Over the past few decades, there has been growing interest in the health benefits of exercise in young people with JIA. However, we are still far from evidence-based exercise prescription for this population. In this review, we give an overview of the available data supporting exercise as a behavioral, non-pharmacological alternative to attenuate inflammation while also improving metabolism, disease symptoms, poor sleep, synchronization of circadian rhythms, mental health, and quality of life in JIA. Finally, we discuss clinical implications, identify gaps in knowledge, and outline a future research agenda.